Thermochemical treatment of sputtered-AlN/2D MoS2 seed layers: a new elaboration process of highly c-axis AlN films - J Patouillard; R Gassilloud; F Mercier; A Dussaigne; B Hyot; M Bernard; S Cadot; N Gauthier; N Vaxelaire; N Bernier; F Martin; C Raynaud; et al. (JPhys Materials)
AlN-based acoustic filters are key devices in radio frequency communications. The AlN material crystal quality on silicon substrates limits the current performances of these devices. Atomic layer deposition -grown 2D-MoS _2 thin film can be used as a template on silicon to improve AlN crystal quality. However, after deposition of thick sputtered AlN films (⩾200 nm), a systematic delamination of the AlN/MoS _2 stack appears, drastically limiting the integration of these materials in RF devices. We propose a new elaboration process to grow thick AlN films with improved crystal quality while avoiding the delamination issue. This process is based on the chemical conversion of the MoS _2 layer through a very thin 5 nm AlN seed using a 1000 °C NH _3 heat treatment at 400 mbar. We show a trade-off between the AlN thickness and the reactive annealing conditions to allow the diffusion of nitrogen towards the underlaying MoS _2 and its conversion into Mo(O _x )N _y . Then, we observe that after the heat treatment, it is still possible to grow thick AlN epitaxial films without any delamination on the substrate while still improving the AlN crystal quality. Using this new route, a 1 µ m thick sputtered AlN layer with a record AlN (002) rocking curve value of 0.71 °C on a silicon-based substrate was obtained without any cracks or delamination.